The Role of Host Genetic Signatures on Root–Microbe Interactions in the Rhizosphere and Endosphere - Yu, Peng; Hochholdinger, Frank (Frontiers in Plant Science, 2018)
Plant associated microbiomes are critical to host adaptation and impact plant productivity and health. A cascade of feedback loops between roots, microbiomes and soil shapes the self-organization of the microbial community associated with the root system. The rhizosphere (i.e. the soil close to the root surface) and endosphere (i.e. all inner root tissues) are critical interfaces supporting the exchange of resources between plants and their associated soil environment. In recent years, high-throughput sequencing technologies have facilitated systemic surveys of root-associated microbiomes and interactions between roots and microbes at the root-soil interfaces. Genetic factors such as species and genotype of host plants are the main drivers of microbial community differentiation and composition. In this mini-review, we will survey the role of these factors on plant-microbe interactions by highlighting the results of next-generation genomic and transcriptomic studies in the rhizosphere and endosphere of land plants. Moreover, environmental factors such as geography and soil type shape the microbiome. Relationships between the root-associated microbiome, architectural variations and functional switches within the root system determine the health and fitness of the whole plant system. A detailed understanding of plant-microbe interactions is of fundamental agricultural importance and significance for crop improvement by plant breeding.